O ajuste de retas pelo método dos mínimos quadrados e secções didáticas de solução LSQ para o ensino médio - Silva, Antônio Everton Sousa da (2015)
Try to represent a line through the data of an experiment, so that it can draw inferences,enables the experience develop important hypothesis about a phenomenon. This work aims to present the method of least squares as a way to find the line that best fits a set of points. For development of this research, it was decided to do a whole literature, allowing to make theoretical survey about some concepts and differential calculus demonstrations, analytical geometry on the straight and linear algebra, as yet, define the method of least squares and apply LSQ solution to resolve an impossible system in the usual sense. Also explored in this study using Excel software as a teaching support tool and its use in the classroom. We finish with a hint of an interdisciplinary lecture on the subject, which in turn, is in an accessible and clear language to the teacher. This class has been developed for teaching steps, in which the latter is performed using Excel software as an auxiliary tool. For a deeper attachment content, we enumerated the end of class several practical exercises.